Phase Demodulation of Short-Cavity Fabry–Perot Interferometric Acoustic Sensors With Two Wavelengths - Hao Liao; Ping Lu; Li Liu; Shun Wang; Wenjun Ni; Xin Fu; Deming Liu; Jiangshan Zhang (IEEE Photonics Journal)
A phase interrogation method for a fiber-optic acoustic sensor based on a short-cavity extrinsic Fabry–Perot interferometer (EFPI) is proposed with two wavelengths. A multichannel tunable optical filter is employed, which selects out two monochromatic beams from the broadband interference spectrum of EFPI with fixed wavelength interval. The influence of the wavelength interval on the recovery of the phase signal has been theoretically and experimentally analyzed. To get the best sensitivity, the wavelength interval is fixed at one quarter of the period of sensor interference fringes. An optimized differential cross multiplication algorithm is utilized to demodulate the acoustic signal, which can eliminate the impact of optical power imbalance between the two light paths. This system may be a universal phase demodulation unit for short-cavity EFPI acoustic sensors. The EFPI acoustic sensing head is formed by an aluminum-attached polyethylene terephthalate membrane and a cleaved fiber tip. The sensor interrogated by the proposed demodulation system demonstrated large dynamic range in low-frequency domain under high sound pressure. A signal-to-noise ratio (SNR) of ∼53 dB is obtained at 80 Hz. These features make the sensor especially suitable for noise detection.